THE INFLUENCE OF USING THE BOOK 'USLUB NAHWU' IN ARABIC LANGUAGE LEARNING TO IMPROVE SPEAKING SKILLS (MAHARAH KALAM) AT SUMATERA THAWALIB PARABEK - Aulia, Rizka; Febrianta, Rita (Program Studi Pendidikan Bahasa Arab, 2025)
One of the main problems in teaching Arabic at this school is that students do not understand Uslub Nahwu (Arabic grammatical style), which causes their speaking skills to remain low. In the textbook Silsilah al-Lughah al-‘Arabiyyah, the material on Uslub Nahwu is mentioned only briefly without examples or clear explanations of how to use it. As a result, students struggle to apply correct grammatical structures in spoken Arabic. Therefore, the researcher aims to implement the “Uslub Nahwu” material in this school so that students can fully understand its forms and applications. This study used a quantitative research method with an experimental approach and a quasi-experimental design. The participants were divided into an experimental class and a control class, using tests and documentation as research instruments. The results showed that the use of Uslub Nahwu had a significant positive effect on improving students’ speaking skills. This was supported by the F-test results (F = 8.652; sig. 0.05) and the t-test results (t = 6.596; sig. 0.000). The findings indicate that the better the students understand Uslub Nahwu, the more their speaking ability improves. Thus, Uslub Nahwu is proven to be an important factor in developing students’ speaking skills in learning Arabic.